Revisiting Digital Gold Ownership from An Islamic Economics Perspective Under Fatwa NO. 166/DSN-MUI/II/2026 - Dzikri Maula Salam; Baidhowi (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2026)
Digital gold has emerged as a technologically mediated investment instrument that converts gold ownership into electronic balances, platform records, or tokenized claims. This article revisits digital gold ownership from an Islamic economics perspective under DSN-MUI Fatwa No. 166/DSN-MUI/II/2026 concerning bullion business activities based on Sharia principles. The study employs normative qualitative legal-economic research using content analysis of the fatwa, supported by recent international journal literature on gold, digital assets, Islamic fintech, Sharia governance, and investor protection. The findings show that digital gold can be treated as a Sharia-compliant economic instrument only when it represents real, standardized, segregated, and auditable physical gold; when ownership reaches al-milk al-tam or legally enforceable complete ownership; when handover occurs through physical qabd or recognized constructive possession (qabd hukmi); and when the contractual architecture avoids riba, gharar, maysir, tadlis, and dharar. The discussion argues that the central issue is not the digital form itself, but the economic substance of ownership, asset-backing, contract certainty, custody, and market conduct. The article proposes an Islamic economics compliance matrix covering underlying assets, ownership, delivery, contract choice, custody, transparency, risk control, consumer protection, and dispute resolution. Digital gold is therefore permissible as a bullion-related innovation when it strengthens lawful wealth preservation, financial inclusion, and market transparency, but it becomes problematic when it merely creates speculative digital exposure detached from real gold or when platform records cannot be redeemed, audited, or legally enforced.